Pelatihan Kewirausahaan Bagi Mantan Pemain Persib Bandung - Kurniati, Fitrina; Mulyani, Heni; Hardiana, R Dian (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2025)
Community Service Activities in the form of Entrepreneurship Training for Former Persib Bandung Players aim to increase interest in entrepreneurship for former football players who are no longer active as professional players. In addition, this activity aims to increase knowledge about preparing a business plan, understanding the importance of branding and social media as a business strategy, and understanding the importance of financial records in business. As workers with a short productive time, this activity is expected to be a provision in retirement. This training was attended by 20 participants, and the results of the activity showed that participants were able to prepare a business plan using the Business Model Canvas (BMC), increase their understanding of the importance of branding and social media as a business strategy and understand the importance of financial records in business. Follow-up activities from this Community Service can be in the form of mentoring for participants who will start their business and expanding the target group of people to football players who are still active as preparation for going through retirement.